Review of Individual, Organizational, and Technological Factors Influencing Knowledge Management Implementatin in Healthcare: A 2019 – 2024 Analysis - Aprilia Romdiyani (Poltekkes Kemenkes Surabaya, 2026)
Comprehending the influencing factors for the implementation of knowledge management in healthcare services is crucial for effectively managing and making use of knowledge to support innovation, decision-making, and improvements in healthcare quality. The purpose of this study is to analyze the key factors influencing the implementation of knowledge management in healthcare services, with the purpose of enhancing service efficiency, accelerating knowledge-based decision-making, and ensuring the quality of patient care. This review followed the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The search was limited to full-text articles published in English between 2019 and 2024 in Scopus and PubMed. A total of 131 articles were initially identified from the databases, including research articles examining factors related to the application of knowledge management. There were data extraction, quality assessment, and the analysis of the data that were conducted for all included studies. A manual content analysis was employed to classify and categorize the identified factors. There were 11 research articles in total that were used in the final review. Content analysis yielded three main groups of factors: (1) individual-related factors, (2) organizational-related factors, and (3) technology-related factors. Conclusion: Healthcare requires robust knowledge management (KM) to support medical team collaboration, best practice sharing, and innovation in patient care.